The Impact of Teacher Social Competence for the Result of Social Subject Grade VIII in SMP Negeri 7 Pematang Siantar - Andre Syahputra Sitohang; Sotarduga Sihombing; Anton Luvi Siahaan (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of teacher social competence on student learning outcomes in social studies subjects in class VIII SMP Negeri 7 Pematang Siantar. The variables in this research are teacher social competence as the independent variable and learning outcomes as the dependent variable. This type of research is quantitative research with a quantitative descriptive data analysis approach, with a research population of all class VIII students at SMP Negeri 7 Pematang Siantar and a research sample of class VIII students at SMP Negeri 7 Pematang Siantar consisting of 146 students selected using simple random sampling ( formula Slovin ). Data collection techniques use questionnaires and documentation. The results of this research show that: there is a positive and significant influence of teacher social competence on learning outcomes. This result can be seen in the t test where the t value is calculated Teacher social competence ( 2.551 ) > t table value (1.65550) which means this variable is significant. The R Square coefficient of determination test was found to be 0.043, which means that 4.30% of the teacher's social competence variable influences student learning outcomes at SMP Negeri 7 Pematang Siantar and the remaining 95.70% is the influence of other variables not examined in this research.